Orchid diversity in Senganan and Angseri Villages, eastern Mount Batukaru Forest, Bali, Indonesia - I PUTU BENNY SANTIKA; IDA AYU PUTRI DARMAWATI; RINDANG DWIYANI; RINI HERMINA KAMUHI (Society for Indonesian Biodiversity, 2026)
Abstract. Santika IPB, Darmawati IAP, Dwiyani R, Kamuhi RH. 2026. Orchid diversity in Senganan and Angseri Villages, eastern Mount Batukaru Forest, Bali, Indonesia. Biodiversitas 27 (7): d270717. https://doi.org/10.13057/biodiv/d270717. Orchid diversity plays an important ecological and conservation role, particularly in forest areas experiencing environmental pressure. However, information on orchids in the eastern forest of Mount Batukaru, Bali, Indonesia, remains limited. This study aimed to assess orchid diversity, community structure, and similarity in Senganan and Angseri Villages, Bali, Indonesia. The study was conducted in the mid-elevation forest zone using the belt transect method. Data were analyzed using species richness, Dominance Index (Di), Shannon-Wiener Diversity Index (H’), Evenness Index (E), and Sørensen Similarity Index. A total of 31 orchid species from 22 genera were recorded, comprising 30 epiphytic and 1 terrestrial species, with 509 individuals. Senganan Village recorded higher species richness (30 species, 321 individuals) compared to Angseri Village (14 species, 188 individuals). Across both sites combined, the dominant species were Dendrobium linearifolium and Bulbophyllum biflorum, which consistently ranked as the most dominant in both villages. The Diversity Index was moderate in both villages (H' = 2.571 in Senganan; H' = 2.318 in Angseri), while evenness was high (E = 0.756-0.878). The Sørensen Similarity Index of 63.64% indicated relatively high compositional similarity between the two sites. Overall, the eastern forest of Mount Batukaru supports relatively high orchid diversity and a stable community structure, underscoring its importance for conservation and sustainable management.